Future Work Self Salience and Future Time Perspective as Serial Mediators Between Proactive Personality and Career Adaptability - Ling, Hairong; Teng, Shanjie; Liu, Xuejun; Wu, Jing; Gu, Xueying (Frontiers in Psychology, 2022)
In recent years, employment has become a growing problem for Chinese college students, who often face issues of “slow employment” and “lazy employment.”. Guided by the framework of career construction theory, we explored how proactive personality strengthens career adaptability. A total of 399 Chinese college students effectively completed the online survey. The results showed a positive correlation between proactive personality, future work self-salience, future time perspective, and career adaptability. Additionally, proactive personality can directly affect career adaptability through three indirect paths: the separate intermediary effect of future work self-salience, future time perspective, and the continuous mediating role of future work self-salience and future time perspective. The results indicate that proactive personality increases career adaptability through the mediating role of future work self-salience and future time perspective. This study contributes to our understanding of the mechanisms underlying the relationship between proactive personality and career adaptability. Additionally, the findings have implications for the career development of college students.